Greenberg's Text-Atlas of Emergency Medicine. - Greenberg, Michael I. (Wolters Kluwer Health, 2011)
Featuring more than 1,100 full-color illustrations, this atlas is a visual guide to the diagnosis and management of medical and surgical emergencies. Emergency medicine depends on fast, accurate interpretation of visual cues, making this atlas an invaluable tool. The book is divided into sections on prehospital management and resuscitation, organ system emergencies, and multisystem emergencies. For each specific emergency, the authors present both clinical photographs and illustrations of significant diagnostic test findings such as specimens, radiographs, endoscopic images, and ECGs. The succ.